Business Performance of Millennial Farmers in the Digital Era Based on Digital Agriculture, Internet Access, and Technology Literacy in East Java - Rani Eka Arini; Christine Riani Elisabeth; Dila Padila Nurhasanah (Westscience Press, 2026)
This study aims to analyze the influence of digital agriculture, internet access, and technology literacy on the business performance of millennial farmers in East Java. The research employed a quantitative approach using a survey method involving 150 millennial farmers as respondents. Data were collected through questionnaires measured using a Likert scale and analyzed using IBM SPSS Statistics. The results indicate that digital agriculture, internet access, and technology literacy have positive and significant effects on business performance both partially and simultaneously. Technology literacy emerged as the most dominant variable influencing business performance, followed by digital agriculture and internet access. The coefficient of determination (R²) value of 0.520 indicates that 52.0% of the variation in business performance can be explained by the three independent variables. The findings suggest that the integration of digital technology, supported by adequate internet access and strong technological competence, contributes significantly to improving productivity, operational efficiency, market expansion, and business sustainability among millennial farmers. This study highlights the importance of strengthening digital infrastructure, expanding internet accessibility, and improving technology literacy to support sustainable agricultural transformation in the digital era.